ChemInform Abstract: Copper‐Catalyzed Skeletal Rearrangements of O‐Propargylic Oximes via Cleavage of a Carbon—Oxygen Bond. Issue 24 (June 2015) - Nakamura, Itaru; Terada, Masahiro
Abstract: Review: [recent developments in copper‐catalyzed skeletal 2, 3‐rearrangement reactions of O‐propargylic oximes to form four‐membered cyclic nitrones, pyridine N‐oxides, and amidodienes via N‐allenylnitrone intermediates; 32 refs.